Pengaruh Model Pembelajaran Inkuiri Terstruktur dengan Pendekatan Saintifik Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Fisika Siswa - Lia Saptini Handriani; Ahmad Harjono; Aris Doyan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This study aims to determine the effect of structured inquiry learning model with scientific approach on studentÃ¢â¬â¢s critical thinking skills and physics learning outcomes of class X in SMAN 1 Gerung in academic year 2014/2015. The study uses a quasi experiment with design untreated control group design with pretest and posttest. The sample was selected by clauster random sampling and obtained class X-3 as the experiment class using structured inquiry learning model with scientific approach and class X-6 as the control class using expository learning model. Data post-test were tested for normality, homogeneity, and hypothesis test. Hypothesis test using t-test polled variance with 5% of significance level. The results of the study were obtained: (1) there was the effect of structured inquiry learning model with scientific approach on studentÃ¢â¬â¢s critical thinking skills and (2) there was the effect of structured inquiry learning model with scientific approach on studentÃ¢â¬â¢s physics learning outcomes ÃÂ This indicates that the structured inquiry learning model with scientific approach is better than the expository learning model. Expected to do further research on structured inquiry learning model with scientific approach that measure the other of higher order thinking skills.